PENERAPAN RESCHEDULING TERHADAP NASABAH PERBANKAN DALAM TERJADINYA KREDIT MACET - Husnaini, Husnaini (Justici, 2023)
Abstract In granting credit, not everything went smoothly, some were substandard and some experienced bottlenecks. thus causing his business to fail and as a result he can no longer carry out his obligations to pay credit installments as they should. In the inability to pay, the bank can carry out three stages, one of which is the rescheduling stage. The problem in this paper is how good faith banking customers are in the event of bad credit. The research in this paper is normative juridical research, which examines only literature or secondary data, which may include primary, secondary and tertiary legal materials. The research in this paper is normative juridical research, which examines only literature or secondary data, which may include primary, secondary and tertiary legal materials. For rescheduling there are several terms and conditions that apply, namely having to re-contract and if there is a delayed margin must be paid in advance at the time of re-contract. The intended re-contract is to carry out the contract as the initial disbursement and pay administrative fees determined by the bank. The implementation of this rescheduling is very helpful for customers in continuing and completing their obligations after being given an extension of the time period in returning financing for bad loans.